Politik Hukum Restorative Justice dalam Pembaruan Hukum Pidana Indonesia: Antara Kepastian Hukum dan Keadilan Substantif - Samuji Samuji (CV. ALIM'SPUBLISHING, 2026)
The reform of Indonesia's criminal law has positioned restorative justice as a key paradigm for resolving criminal cases by emphasizing the restoration of victims, offenders, and society rather than focusing solely on punishment. Nevertheless, its implementation continues to encounter significant normative challenges, particularly regarding legal certainty, consistency of application, and the scope of authority exercised by law enforcement agencies. The coexistence of various legal instruments governing restorative justice has created inconsistencies that may lead to disparities in law enforcement and undermine the objectives of national criminal law reform. This study aims to examine the legal policy of restorative justice within Indonesia's criminal justice system and to analyze its role in balancing legal certainty with substantive justice. This research employs normative legal research using statutory, conceptual, and comparative approaches. Legal materials were collected through library research and analyzed using a prescriptive legal method. The findings indicate that the legal policy of restorative justice reflects a paradigm shift from retributive justice toward a restorative criminal justice system that prioritizes social reconciliation and the protection of the rights of all parties. However, its effective implementation requires regulatory harmonization, clearer operational guidelines, and stronger legal certainty to prevent inconsistent discretionary practices among law enforcement institutions. This study proposes a legal policy model that integrates substantive justice with legal certainty to strengthen the implementation of restorative justice within Indonesia's criminal justice system.